Differentiated routes to vulnerability: Marital status, children, gender and poverty. (September 2021) - Herbst-Debby, Anat; Endeweld, Miri; Kaplan, Amit
Highlights: Widowhood/divorce differentially affect poverty risk, based on gender and children. Divorce decreases the risk of poverty for men, while it increases it for women. Widowhood tends to increase poverty for men, but only for women does the poverty risk increase as the number of children rises. The combination of divorce and children increases poverty among both genders, but seems to be more so for mothers. The group with the highest poverty risks following marital dissolution is divorced mothers with two or more children. Abstract: This study compares poverty risks between two types of transition involving family status, which the life course perspective considers risky events: divorce and widowhood. The case study is Israeli society, characterized by high fertility rates and a high risk of poverty. The study examines the relationship between marriage dissolution and the risk of poverty, distinguishing between divorce and widowhood, and how they are affected by the intersection of gender and number of children in the household. Based on unique administrative panel data, we studied all women and men in Israel, aged 18–60 in 2003, who married in 2003 and were widowed or divorced by 2015, as well as a random sample of 20 % of all women and men in Israel who married in 2003 and remained married until 2015. Fixed effects models calculated the probability of women and men becoming poor. Results revealed a gendered effect of entering into poverty that largely depends on how the marriage ended and the number of children in the household. Divorce increases poverty risks for women and decreases them for men. However, for both genders, the combination of divorce and more children at home increases poverty. In contrast, widowhood tends to increase poverty for men, but only for women does the poverty risk increase as the number of children rises. Findings are discussed in the context of high fertility rates, Israeli welfare policy and the economic vulnerability associated with parents' childcare responsibilities.